The impact of previous prostate biopsy on the outcomes of bipolar transurethral enucleation of the prostate: a retrospective cohort study - Hussein Mamdoh; Ayman Mousa; Ahmed Eissa; Khaled Almekaty; Tarek Gameel; Maged Ragab; Mohamed Abo El-enen; Ahmed Zoeir (African Journal of Urology, 2025)
Abstract Background In patients who have undergone previous prostate biopsies, surgeons are worried that enucleation may be challenging due to potential adhesions, hematoma, and fibrosis between adenoma and prostatic capsule. Therefore, we aimed in this study to evaluate the impact of previous prostate biopsy on the technique of bipolar transurethral enucleation of the prostate (B-TUEP) and also, to detect the ideal time interval between biopsy and enucleation of the prostate. Methods The data of 125 patients who underwent (B-TUEP) were retrospectively reviewed. Patients were stratified into two groups; group A (no previous biopsy) (n = 93) and group B (n = 32) had undergone previous prostate biopsy. Enucleation time, overall operative time, enucleation efficacy and complications were compared in both groups. Results The median age of our patients was 67 (56–76). The enucleation and overall operative time (OT) were significantly longer in group B than in group A (p < 0.001). The overall post-operative complications rate was higher in group B (40.6%) than in group A (7.5%, p < 0.001). There was no significant difference as regards the post-operative IPSS, Q-max and PVR in both groups. Time interval (less than 2 weeks) between the prostate biopsy and enucleation was significantly associated with a higher post –operative complications. Conclusion Previous prostate biopsy (PB) before (B-TUEP) has been associated with significantly longer enucleation time and higher complications rate when compared to patients without previous biopsy. A time interval more than 2 weeks (between biopsy and enucleation) is crucial to improve the outcomes and reduce the complications.